INCREASE OF IMMUNITY CANTIK HYBRID GROUPER JUVENILES BY LIPOPOLYSACCHARIDE (LPS) - Des Roza (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Disease is one of obstacle in fish culture. Immunity of fish against disease can be increased by using immunostimulant. The purpose of this experiment to increasing immunity of cantik hybrid grouper (cross breeding of tiger grouper, Epinephelus fuscoguttatus female with marbled grouper, E. polyphekadion male) to the diseases by using immunostimulant. Treatments were LPS cell walls of V. alginolyticus and commercial LPS was also used in this study, as a-control without LPS was used saline water (0.85% NaCl). The LPS was delivered by injection intra-muscularly with concentration of 0.1 mL/fish. This experiment was design by completely randomized with 3 replicates. Results showed that LPS were effective to increase titer antibody values and survival rates of cantik hybrid grouper. The titer antibody values of fish after 90 days rearing period were 128 (LPS from V. alginolyticus), 64 (commercial LPS), and only 4 in the control fish. The survival rates at the end of experiment were 88.67 ± 3.62% (LPS from V. alginolyticus), 85.22±5.93% (commercial LPS), and only 50.13 ± 6.11% in the control fish. Relative percentage survival of fish following challenged with live V. alginolyticus were 77.46% in the received LPS from V. alginolyticus cell wall and 71.12% in the fish received commercial LPS. It is suggested that LPS effective to increase immunity of cantik hybrid grouper against bacterial infection. Keywords:  cantik hybrid grouper, immunity, lipopolysaccharide, Vibrio alginolyticus